Aproveitamento de plantas espontâneas (aromáticas e mediciais), em montado de sobro - Lopes Borges, A. E.; Afonso Morais, M. H.; Bernardo, A.; Azevedo Gomes, A.; Saraiva Lopes, A. M. (Scientia gerundensis, 1992)
In a previous paper the phenological evolution of aromatic and medicinal species in the understory of open forest of cork oak was studied, localised in two <<vis-a-visn hillsides with NW and SE exposition in Odemira. In this paper the effect of exposition in biological cycle of species is apreciated. A comparative analysis between the vegetation of the two stations was made in funtion of the phenological evolution, biomass prodution, floristic list and recovery by species. The characteristic of the organic and inorganic fractions are emphasized related with the present phenophases.
Keywords: aromatic plants; biomass; cork-oak stands; Medicinal plants; Phenology